THE EFFECT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON TEACHER TURNOVER INTENTION IN X INSTITUTION IN PALEMBANG - Suwantono Kusuma, Iwan; Lin Yan Syah (Dinasti International Journal of Management Science, 2020)
The purpose of this researches to gain proper knowledge concerning the influence of Job Satisfaction and Organizational Commitment on Turnover intention in X Institution of Palembang. This study used a survey which studied data from sample taken from the distribution of questionnaires to 92 respondents with details of 30 people as test sample and 62 respondents as research sample. Data were analyzed using structural equation modeling (SEM) methods. The results showed that the t-value for job satisfaction is 4.79 (> 1.96) resulted in negative which means there are significant effect of job satisfaction on turnover intense. T-value for organizational commitment is 3.19 (> 1.96) resulted in negative which means there are significant effect of organizational commitment on turnover intense.